Geomorphing effect of sand fences in primary dunes of Gulf of Riga - Lapinskis, Jānis (Landscape Architecture and Art, 2022)
Finding a the most appropriate solution for the problems caused by coastal eros ion is very important, as erosion prevention and habitat management measures must promote the restoration of the natural balance (order of things before anthropogenic disturbances) and restore the coastal status quo as much as possible [6; 2]. Dune fences are a very widespread erosion management tool on developed sandy coastal areas due to ease of installation, inexpensiveness, and generally positive public attitude [1]. Effectiveness and impact of fences have also been studied in many places around the world, however previous studies in Latvia have been very limited and episodic [16]. This article shows the observed dune and high beach area evolution of the coast in Riga, a somewhat developed coastal section on the top of the Gulf of Riga, Latvia, over a 4-year period from 2017 to 2020. Dune fences were installed along several short, but significantly disturbed sections of coast in 2018 and 2019. Implementation area is one of the busiest parts of the coast of Latvia dealing with the highest level of anthropogenic disturbance. Data has been derived from cross-shore transects (n=12) along the 17 km long coastal section between Daugava and Gauja river mouths. The findings generally indicate a very intense initial wind driven sand accumulation in the target areas compared to the background situation. It also seems that such a method may in the longer term be responsible for reduction of the primary dune height and beach width.